2021
DOI: 10.2147/eb.s305822
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Proton Beam Therapy for Primary Optic Nerve Sheath Meningioma

Abstract: Purpose Management of optic nerve sheath meningiomas (ONSM) remains challenging. Photon radiation therapy (PhRT) is the most common treatment for sight-threatening ONSM. Proton beam therapy (PBT) is less commonly used because it is more expensive and because there are questions about its efficacy specifically in relation to ONSM. PBT has the theoretical advantage of reducing radiation exposure to adjacent structures. We report the visual outcome of patients with primary ONSM managed at the Fondati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…No significant association was found between the tumor’s prescribed dose and radiation retinopathy prevalence ( p = 0.714). Of these 29 studies, 4 studies reported the prescribed dose to the retina [ 1 , 26 , 33 , 39 ], 6 studies reported the prescribed dose to the optic nerve [ 27 , 33 , 44 , 45 , 46 ], and 5 studies reported the prescribed dose to the chiasm [ 27 , 28 , 33 , 38 ]. No significant association was found between retinopathy prevalence and the dose received by the retina ( p = 0.798) and optic nerve ( p = 0.366).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No significant association was found between the tumor’s prescribed dose and radiation retinopathy prevalence ( p = 0.714). Of these 29 studies, 4 studies reported the prescribed dose to the retina [ 1 , 26 , 33 , 39 ], 6 studies reported the prescribed dose to the optic nerve [ 27 , 33 , 44 , 45 , 46 ], and 5 studies reported the prescribed dose to the chiasm [ 27 , 28 , 33 , 38 ]. No significant association was found between retinopathy prevalence and the dose received by the retina ( p = 0.798) and optic nerve ( p = 0.366).…”
Section: Resultsmentioning
confidence: 99%
“…Optic neuropathy was observed in 319 patients (prevalence = 2.0% [CI 95% = 0.028–0.034]). The diagnosis time of optic neuropathy was reported in 35 studies, with a mean of 36 months following irradiation (range, 3–108 months) [ 1 , 19 , 22 , 26 , 28 , 35 , 39 , 40 , 41 , 42 , 43 , 45 , 49 , 51 , 52 , 54 , 55 , 59 , 60 , 61 , 62 , 65 , 71 , 73 , 75 , 77 , 79 , 81 , 85 , 87 , 89 ]. Optic neuropathy prevalence was observed at prescribed doses of >50 Gy and <50 Gy at 4.5% and 1.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proton beams achieve this through a finite range and narrow beam. A retrospective study by Hage et al 21 looked at 60 patients who underwent PBT for primary ONSMs and found that 85% had either improvement or stability in their visual field examination. Among the 31 patients who underwent PBT alone without surgery in their cohort, 4 developed radiation retinopathy, of which 2 were mild with no change to visual acuity, and no patients developed a definitive radiation optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%